Gastric syphilis: The great imitator in the stomach - Okamoto, Koh (IDCases, 2018)
Syphilis is resurging worldwide. Here, we present the case of a 33-year-old heterosexual man who presented with a 3-week history of epigastric pain, nausea, emesis, and 8 kg weight loss. He was subsequently diagnosed with gastric syphilis, based on reactive syphilis serological testing and Treponema pallidum found in gastric biopsy specimens. Gastric syphilis is a rare presentation observed in 1% of cases and usually develops in secondary syphilis. Given the nonspecific manifestation and findings, a high index of suspicion is required for diagnosis of gastric syphilis.